Contextualizing Teacher Professionalism: Findings from a Cross-Case Analysis of Union Active Teachers - Osmond-Johnson, Pamela (Alberta Journal of Educational Research, 2017)
This paper draws on data collected as part of a study of the discourses of teacher professionalism amongst union active teachers in the Canadian provinces of Alberta and Ontario. Interviews revealed a triad of influences on the professionalism discourses of participants: engagement in teacher associations, the larger policy environment, and teacher agency. The manner in which this triad played out in each case, however, was unique to the particular political and organizational contexts framing the spaces in which such discourses were created. Using cross-case analysis, this paper specifically highlights the complex and contextualized nature of teachers’ conceptions of professionalism, paying particular attention to the nuanced enabling and limiting conditions identified between the cases. Cet article s’appuie sur des données recueillies dans le contexte d’une étude portant sur le discours concernant le professionnalisme des enseignants actifs dans leur syndicat et vivant dans les provinces canadiennes de l’Alberta et de l’Ontario. Les entrevues ont révélé une triade d’influences sur ce discours chez les participants : l’implication dans des associations d’enseignants, le contexte politique général et l’agentivité des enseignants. L’interaction de ces composantes s’est déroulée d’une façon distincte selon le contexte politique et organisationnel du milieu dans lequel le discours a été créé. S’appuyant sur une analyse transversale, cet article souligne la nature complexe et contextualisée des conceptions qu’ont les enseignants du professionnalisme, et se penche particulièrement sur les conditions nuancées, favorables ou restrictives, qui ont été identifiées dans chaque cas.